Pengaruh Literasi Keuangan dan E-Money Terhadap Perilaku Keuangan Generasi Z Cashless Society Terhadap Mahasiswa Manajemen UBP Karawang - Umniyah; Wanta; Dwi Epty Hidayaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of financial literacy and the use of e-money on the financial behavior of Generation Z in a cashless society and pay later or periodic online loans which make it easier for users to carry out transactions when the user needs but does not have enough money when needed. Especially for UBP Karawang Management students. This research stage involves testing validity and reliability using quantitative descriptive verification methods. to analyze financial literacy, e-money and financial behavior variables. The results show that the questions in the questionnaire are proven to be valid and reliable. Multiple linear regression analysis reveals that financial literacy and e-money together significantly influence the financial behavior of Generation Z. The partial test shows that financial literacy and labor have a significant influence on financial behavior, while financial behavior influences e-money. The implications of this research include the importance of increasing financial literacy, e-money development, and the role of financial behavior in supporting students. The conclusion highlights that these three variables together have a significant influence on Generation Z's financial behavior, with financial literacy contributing 19.3%, while the rest is explained by other factors. This research offers an in-depth view of the complexity of the relationship between financial literacy, e-money, and Generation Z's financial behavior in the cashless era.